2015
DOI: 10.1021/acs.langmuir.5b02673
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Marangoni Flows on the Shape of Thin Sessile Droplets Evaporating into Air

Abstract: Freely receding evaporating sessile droplets of perfectly wetting liquids, for which the observed finite contact angles are attributed to evaporation, are studied with a Mach-Zehnder interferometer. The experimentally obtained droplet shapes are found to depart, under some conditions, from the classical macroscopic static profile of a sessile droplet. The observed deviations (or the absence thereof) are explained in terms of a Marangoni flow due to evaporation-induced thermal gradients along the liquid-air int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 33 publications
6
61
0
1
Order By: Relevance
“…The integrals in (95) are computed in Matlab with the same methods used in the evaluation of (32). We plot the composite evaporation rate (95) as a function of r for Pe k = 10 1 , 10 2 , 10 3 , 10 4 in Fig.…”
Section: Validation Of Asymptotic Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The integrals in (95) are computed in Matlab with the same methods used in the evaluation of (32). We plot the composite evaporation rate (95) as a function of r for Pe k = 10 1 , 10 2 , 10 3 , 10 4 in Fig.…”
Section: Validation Of Asymptotic Resultsmentioning
confidence: 99%
“…The resulting finite linear algebraic system is then solved using Matlab's backslash command (since the system is symmetric positive definite, this uses Cholesky factorization). Once the coefficients a n (Pe k ) have been determined numerically, the evaporation rate E(r ) is approximated by (32) with the sum truncated at n = M * (Pe k ). The integral in (32) is evaluated numerically using the integral command in Matlab.…”
Section: Computing the Evaporation Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Effect of gravity on evaporation has to be considered in space applications. In recent paper [5] it is shown that Marangoni effect (flow driven by surface tension gradient) modifies the drop interface shape and impacts on evaporation. Deep understanding of evaporation requires knowledge what is happening inside droplet.…”
Section: Introductionmentioning
confidence: 99%
“…2) by approximately one order of magnitude. Yet, it appears that the overall trends are well captured by this rather simple model ignoring viscous friction on the pillars and tortuosity of the porous structure (in addition with non-isotropy, pinning, convective effects in the gas affecting the evaporation rate [29], cooling and Marangoni effects [30] . .…”
mentioning
confidence: 97%